The transregional dimension of territorial knowledge management. An evolutionary perspective on the role of universities - Ruediger Wink (European Regional Science Association (ERSA), 2002)
During the last decades, research on regional innovation processes has turned its focus on the relevance of knowledge as a decisive factor to explain regional growth. New Economic Geography as well as new models of regional economics stressed the advan-tages of unique regional structures with locally bounded knowledge and systems to ex-change experiential knowledge via different forms of direct communication. Network effects lead to advantages of metropolitan regions within international competition. From an evolutionary institutional economics' perspective, the development and changes of formal and informal institutional arrangements have to be investigated, enabling regional actors to co-operate on a medium-to-long-term basis and overcoming free-rider incentives and cognitive barriers to identification of tacit knowledge. For uni-versities, two important functions within these knowledge networks occur. Firstly, universities serve as sources for new research experiences. Secondly, universities 'produce' highly skilled human capital, increasing directly the absorptive capacity of the region and making it easier for regional companies to get access to this mobile group. It is the first objective of the proposed paper to explain this role within an approach to deal with knowledge on a regional level called 'Territorial Knowledge Management'. This intraregional perspective, however, reflects only one side of the 'coin' of success-ful regional knowledge networks. Without interregional exchange of experiential knowledge, risks of functional lock-in-processes increase leading to policies of preventing necessary structural changes and incentives for companies and highly skilled persons to leave the regions. But learning by interregional exchange of knowledge can only be realised successfully if interpersonal face-to-face contacts and common communication structures and codes exist. Within regions, implicit institutions like trust and reciprocity help to overcome barriers to build up network structures but depend on a 'closeness' of networks. Therefore, interregional knowledge networks require new (and specific) institutional arrangements. Geographical proximity will be less important for interregional knowledge transfers than institutional and cultural proximity, which has a direct influence on cognitive structures within companies, R&D institutes and universities. What is the special role of universities in this context, and how can universities react to new challenges of interregional openness? These are the leading research questions of the proposed paper. As international competition increases in markets for education and research, universities have to strengthen their specific core competencies and look out for suitable strategies. The paper shall give hints how and why these strategies have to be coordinated with activities within regional knowledge networks. Four university-specific strategies to promote interregional transfer of knowledge are presented and analysed, representing different objectives, target groups and instruments: strategic ap-pointments of foreign professors, further international co-operation in the fields of research, courses and degrees, internationalisation of research and education by building up international franchise systems, and strengthening alumni networks. These strategies are investigated on the basis of a theoretical (evolutionary) model as well as by giving a survey on existing case studies. It is not the objective of the paper to evaluate the impact of these strategies for universities alone, but for regional processes of generating, applying, diffusing, and adapting knowledge, and for the emerging geographical pattern of interregional co-operation in the enlarging Europe. Finally, prerequisites are identified to secure positive impact of university's internationalisation strategies on regional absorptive capacities.
Keywords: 330